2022
DOI: 10.1177/23259671221083318
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Combined Lateral Meniscus Posterior Root Repair and Anterior Cruciate Ligament Reconstruction

Abstract: Background: Lateral meniscus posterior root tears (LMPRTs) almost always occur in association with anterior cruciate ligament (ACL) tears. Their repair is advocated to restore the stabilizing and load-sharing functions of the meniscus. Purpose: To study the functional outcomes of combined arthroscopic repair of LMPRTs and ACL reconstruction (ACLR). Study Design: Case series; Level of evidence, 4. Methods: The authors evaluated patients who underwent simultaneous arthroscopic ACLR and LMPRT repair. All patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…recommended drilling independent tunnels for the LMPHR and the ACL graft, with the emphasis on keeping an adequate bony bridge between the two tunnels. 9 …”
Section: Discussionmentioning
confidence: 99%
“…recommended drilling independent tunnels for the LMPHR and the ACL graft, with the emphasis on keeping an adequate bony bridge between the two tunnels. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Qian et al [29] reported MRI could detect only 33% of LMPRTs in a series of 45 arthroscopically confirmed tears. Furthermore, Shekhar et al [34] series demonstrated only 13 patients (52%) of the group with LMPRT confirmed by arthroscopy had a preoperative MRI reporting a tear in the posterior lateral meniscus, 5 of which were diagnosed as definitive root tears and 8 of which were diagnosed as a posterior horn tear.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical repair of the meniscal root is important for its function in converting femorotibial loads into circumferential tension [ 19 ]. We, therefore, drilled the additional tunnel aiming at the posteromedial direction from the lateral tibial eminence and anterior from the PCL, as previously described [ 8 , 20 ]. One concern regarding the additional tunnel was tunnel convergence with ACL tunnels [ 21 ]; however, in our case, only a 2.4 mm tunnel was needed to pass the suture, and enough margin had been confirmed ( Figure 2(f) ).…”
Section: Discussionmentioning
confidence: 99%